Tradisi dan Perubahan Budi Daya Pohon di Desa Rambahan Kuansing dan Desa Ranggang Tanah Laut - Didik Suharjito (Jurnal Manajemen Hutan Tropika, 2011)
The phenomenon of widespread tree cultivation by local community in some countries during the last three decades has been explained by researchers with a macro perspective. This study is to understand the phenomenon at the micro level and from the native (peasant or farmer) point of view. This study aims to explain the tradition and changes in tree cultivation. Theoris economic system were used as the basis to explain the tradition and changes in tree cultivation in Rambahan village community of the Kuansing District and Ranggang Village community of Tanah Laut District. Case study method was used in this study. The data were collected from informants through individual interviews and focused group discussions. The results of this study show that the cultivation of trees has been practiced and institutionalized in the everyday lives of local people and passed down from generation to generation, as well as a source of socio-economic stability of families. Factors that farmers take into consideration in the selection of tree crops to be cultivated are price, easy to sell, harvesting intensity, knowledge and skills, labor availability (particularly family labor), and capital availability. The results of this study also indicate that some elements of the economic system of Ranggang and Rambahan communities have the characteristics of capitalism adherent, while some other elements have the characteristics of pre-capitalism. In other words, two communities are in a transition between pre-capitalism and capitalism as shown in the practice of tree cultivation.